2005
DOI: 10.1051/0004-6361:20042425
|View full text |Cite
|
Sign up to set email alerts
|

HST/STIS low dispersion spectroscopy of three Compact Steep Spectrum sources

Abstract: Abstract. We present Hubble Space Telescope Imaging Spectrograph long-slit spectroscopy of the emission line nebulae in the compact steep spectrum radio sources 3C 67, 3C 277.1, and 3C 303.1. We derive BPT (Baldwin-Philips-Terlevich; Baldwin et al. 1981) diagnostic emission line ratios for the nebulae which are consistent with a mix of shock excitation and photoionization in the extended gas. In addition, line ratios indicative of lower ionization gas are found to be associated with higher gas velocities. The … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
59
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(71 citation statements)
references
References 38 publications
12
59
0
Order By: Relevance
“…This also supports the claim that the shock contribution to [O iii] luminosity may not be important, and the [O iii] luminosity can still be regarded as a good indicator of central thermal emission in these small radio-sized GPS sources. Labiano et al (2005) found that the contribution to narrow line luminosity from the shocked gas is between 30% and 70% for the CSS source 3C 303.1, and this ratio is even lower in other two CSS sources (3C 67 and 3C 277.1), based on the ionization diagnostics of different narrow emission lines. Therefore, the bolometric luminosities of nine CSS sources calculated from the [O iii] luminosities may not be overestimated too much, which will not change our main conclusion.…”
Section: Summary and Discussionmentioning
confidence: 93%
“…This also supports the claim that the shock contribution to [O iii] luminosity may not be important, and the [O iii] luminosity can still be regarded as a good indicator of central thermal emission in these small radio-sized GPS sources. Labiano et al (2005) found that the contribution to narrow line luminosity from the shocked gas is between 30% and 70% for the CSS source 3C 303.1, and this ratio is even lower in other two CSS sources (3C 67 and 3C 277.1), based on the ionization diagnostics of different narrow emission lines. Therefore, the bolometric luminosities of nine CSS sources calculated from the [O iii] luminosities may not be overestimated too much, which will not change our main conclusion.…”
Section: Summary and Discussionmentioning
confidence: 93%
“…12. 5 objects in our GPS sample have spectroscopic O[iii] measurements (O'Dea 1998; Labiano et al 2005Labiano et al , 2008, and references therein). The "control sample" is a collection of Seyfert 2-galaxies measurements in Guainazzi et al (2005).…”
Section: The X-ray Obscuring Environmentmentioning
confidence: 99%
“…de Vries et al (1998Vries et al ( , 2000 showed that the hosts are old giant ellipticals. Interactions of the radio source with the galaxy interstellar medium are clear from the study of the emission lines (see, e.g., Labiano et al 2005;Holt et al 2009). The presence of young stellar populations in these objects has been revealed several times (Holt 2009;Labiano et al 2008;deVries et al 2007;Tadhunter et al 2002).…”
Section: Introductionmentioning
confidence: 99%